PG15 Peri-mortem caesarean section – are we doing it right? Live drills with the development and simulation hub (DaSH) at Northern Lincolnshire and goole NHS trust (NLaG). (10th November 2020) - Harrison, Nick; McGuffie, Rochelle; Quayle, Alexandra
Abstract : Background: Maternal cardiac arrests are extremely rare, occurring in approximately 1:12, 500 pregnancies, 1 hence most Obstetricians are unlikely to encounter this situation. The physiological and physical changes in pregnancy necessitate amendments to the cardiac arrest algorithm to ensure appropriate decision making and best outcomes for mother and foetus. The Royal College of Obstetricians and Gynaecologists 2 recommends, a peri-mortem caesarean (PMCS) is performed within 5 minutes of collapse. However the prospect of performing a PMCS remains challenging regardless of healthcare professional status. The Development and Simulation Hub analysed current practice and resources in the Emergency Department of our two secondary acute care hospitals. Method: A high fidelity manikin was loaned, to accurately replicate the surgical aspect of the procedure. With support of Clinical and Governance Midwives, a maternal cardiac arrest scenario was run as an unannounced live drill, analysing: Team response with cardiac arrest management of a term pregnancy. Delivery of foetus within 5 minutes of cardiac arrest. Human factors concentrating on decision making, teamwork, communication, equipment utilisation and situational awareness. Results: Observation analysis was conducted by the Clinical Skills Midwife and Simulation Lead. Effective debriefing identified the following findings and recommendations: Need for strong leadership and closed loop communication in clinical emergencies Difficulty taking the decision to perform PMCS–' taking the plunge' All Obstetric and Emergency Medical staff to receive updates on PMCS in maternal resuscitation Development of standard operating procedure for PMCS Designated maternal trolley within ED is stocked signed off by dedicated Maternity Team Streamlining the surgical pack Close liaison with Labour Ward Co–ordinator ensuring effective resource deployment Dedicated maternal scribe book All midwifes carrying emergency bleep to have access to ED via ID badges Consider change of uniform for maternity staff so can be clearly identified as a Midwife within emergency situations Regular live drills to assist with confidence/competence and reassess whether learning points have been actioned. Impact on Patient Care: The identification of latent risks in equipment, resources and staffing as well as confidence with protocols and decision making has allowed us to tackle these issues. Streamlined and checked equipment, as well as regular drills and revisiting, will improve collaborative team knowledge and skills when faced with a very difficult and rare clinical scenarios. Strict adherence to the RCOG protocol will give the chance of better outcomes for mother and baby. References: Mothers and Babies: Reducing risk through audit and confidential enquiries across the UK (MBRRACE-UK). https://www.npeu.ox.ac.uk/mbrrace-uk/reports. Accessed Nov.2019 Maternal Collapse in Pregnancy and Puerperium. Green-top Guideline No56. (2011) Royal College of Obstetricians and Gynaecologists. https://www.rcog.org.uk/guidelines-research-services/guidelines/gtg56. Accessed Nov. 2019.